DARI MANAJER MENJADI PEMIMPIN PENGAJARAN: Perubahan Peran Kepala Sekolah - Syarwan Ahmad (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2013)
Instructional leadership is a concept in which a principal’s management emphases on academic or instructional improvement. It is the principal leadership siding with academic affairs. Conventionally, school principals play the role as managers or administrators. Whereas the role of instructional leadership is delegated to other parties such as vice principal for curriculum affairs. Most educators and scholars agree that instructional leadership needs to be practiced if effective schools are to be realized. To be an instructional leader, it is necessary for a principal to have expertise in curriculum, instruction and assessment. Since most principals lack of skills on instructional leadership practices, instructional leadership training for principals is badly needed.